Safe and Secure PIC Based Remote Control Application for Intelligent Home - Erol, Yavuz; Balik, Hasan H.; Inal, Serkan; Karabulut, Duygu (Int Journal Computer Science & Network Security-Ijcsns, 2007)
In this paper, secure PIC based remote control system for intelligent houses has been presented. With this implemented system, it is possible to safely control electricity operated domestic devices by the help of public or mobile phones from any places all over the world. Developed remote control device has been optically and electrically isolated to secure the system. In addition the system implemented and introduced in this paper has pin-check algorithm in order to enlarge security.
Keywords: Intelligent home; DTMF; PIC microcontroller; telephone line